Prevalence of anti- beta2GPI antibodies and their isotypes in patients with renal diseases and clinical suspicion of antiphospholipid syndrome - Sabiha Anis; Ejaz Ahmed; Rana Muzaffar (Society of Diabetic Nephropathy Prevention, 2013)
Background: Antiphospholipid antibodies (aPL) are autoantibodies that are associated with a clinical state of hypercoagulability and diverse clinical manifestations collectively known as antiphospholipid syndrome (APS). Objectives: To investigate the prevalence of anti-beta2glycoproteinI-antibodies (anti-β2GPI) and their isotypes in patients with renal diseases and clinical suspicion of antiphospholipid syndrome (APS). Patients and Methods: This is a retrospective study in which we have analyzed the prevalence of anti-β2GPI and its isotypes in 170 patients on initial testing and in 29 patients repeated after 12 weeks for confirmation of APS. The clinical information was provided by the treating physicians or retrieved from the clinical records. The tests for anti-β2GPI screening and its isotypes (IgG, IgM and IgA) detection were assessed. Results: On initial samples, anti-β2GPI was positive in 118patients. IgA-β2GPI positivity (93; 79%) was significantly higher than IgM and IgG isotypes. Out of anti-β2GPI positive patients, clinical features in 95 patients were suggestive of APS or had SLE. Of these, IgA isotypes was found in 66% (P = 0.010), IgM in 31% (P = 0.033), and IgG in 11% (P = 0.033). On repeat testing, anti-β2GPI was persistently found In 22 patients with a continual predominance of IgA-anti-β2GPI over IgM and IgG isotypes (91% vs. 45.5% and 18% respectively). Conclusions: Our results show that IgA-anti-β2GPI antibodies are the most prevalent isotypes in patients with renal disease or on renal replacement therapy in our population. Thus inclusion of IgA-anti-β2GPI in the testing repertoire may increase the diagnostic sensitivity for APS in patients with renal diseases.